The prognostic significance of E-cadherin expression in laryngeal squamous-cell carcinoma: a systematic review - RE, M. (Acta Otorhinolaryngol Ital, 2018)
The aim of this study was to systematically review publications that investigated the prognostic role of E-cadherin immunostaining in patients affected by laryngeal squamous cell carcinoma. An appropriate string was run on PubMed to retrieve articles dealing with this topic. A double cross-check was performed on citations and full-text articles by two authors independently to analyse all manuscripts and perform a comprehensive quality assessment. Among 89 abstracts identified, 13 articles were included. These studies reported on 1,121 patients with histologically confirmed diagnosis of laryngeal squamous cell carcinoma. Overall, there were 10 studies that showed a significant correlation between E-cadherin immunohistochemical expression and at least one of the clinical and histopathological parameters considered by the authors. In particular E-cadherin expression was significantly associated with N stage (five studies), grading (four studies) and disease-free survival/disease-specific survival (six studies). In conclusion, the findings of our review appear similar to the results published by other authors on the putative role of E-cadherin in progression of malignancy. In fact, for laryngeal squamous cell carcinoma it seems that lower levels of E-cadherin correlate with increased tumoural aggressiveness and worse prognosis. Nevertheless, further high-quality prospective studies should be carried out to clarify if E-cadherin expression may be considered as an independent prognostic factor for patients affected by laryngeal cancer.